The prevalence of relative age effects in a nationwide analysis of racket sports: Happy birthday? - Bilgiç, M.; Güvenç, A. (PLOS ONE, 2024)
Relative age effects (RAEs) refer to all consequences of chronological age-based systems. The purpose of this study was to investigate the prevalence of RAEs among Turkish racket sports players. As a nationwide analysis, the present study extends beyond the typical investigations of elite-level popular sports by examining RAEs in racket sports players from the lowest grassroots level to the top and from children to veteran athletes. A total of 57476 racket sports players (i.e., badminton, squash, table tennis and tennis) were evaluated in the study. To investigate interquartile distributions, Chi-square goodness-of-fit tests were used. Odds Ratios (OR) and 95% Confidence Intervals (95% CIs) were calculated to compare quartiles. Poisson regression with canonical link was conducted to analyze the count data. A statistically significant difference in the prevalence of RAEs was noted in both genders and in total sample. The ID in Poisson regression shows that players born at the beginning of the year are 1.63 more likely to be represented than those born at the end of the year. Considering the sports separately, statistically significant distribution bias was found in badminton, table tennis and tennis but not in squash. Moreover, regarding the age categories, the peak RAEs were noted in the youngest age category of tennis as 30.6% of players were in Q1 while only 17.4% were in Q4. Such findings have been discussed with different moderators, hypotheses and models such as the developmental systems model, social agents, psychological issues, and the role of selection processes by coaches. In conclusion, process (i.e. athlete development process) is suggested to be focused instead of a point in the continuum for selection and scouting practices, which may ensure avoiding talent loss and sports drop-out and establishing quality sport participation environments for all.